Child Violence in Online Learning Time - Syamsiah Badruddin; Okis Mulyatina (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2021)
Acts of violence against children is a behavior that is wrong whatever the reason. Because acts of violence against children have a bad impact on children's emotional, psychological growth and development, to the formation of children's personalities that are not good. During the process of implementing online learning which is completely done at home. The family is the main key in carrying out the role of education as a right that must be given to children. The condition of learning loss in elementary school students that occurs results in reduced children's potential and abilities. This study was conducted to determine the interactions that are built in the family during the application of online learning. To find out acts of violence that can be carried out in the family and the direct impact on children. Through descriptive qualitative research in explaining phenomena and triangulation of sources as a method in obtaining data that actually occurs in the field. The results of this study indicate that parents have difficulty in dealing with the implementation of online learning, which often encourages them to be emotional and take acts of violence verbally or even physically. This results in children not getting the maximum learning process at home.